Effect of crystal packing on the thermosalient effect of the pincer-type diester naphthalene-2,3-diyl-bis(4-fluorobenzoate): a new class II thermosalient solid - Tamboli, Majid I.; Karothu, Durga Prasad; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Naumov, Pance (Chemistry-A European Journal, 2018)
The pincer-like double ester naphthalene-2,3-diyl-bis(4-fluorobenzoate) (2) is pentamorphic. Upon heating crystals of form I to below their melting point (441-443 K), they undergo a phase transition accompanied by a thermosalient effect, that is, rare and visually striking motility whereby the crystals jump or disintegrate. The phase transition and the thermosalient effect are reversible. Analysis of the crystal structure revealed that form I is a class II thermosalient solid. Crystals of form III also underwent a reversible phase transition in the temperature range of 160 to 170 K; however, they were not thermosalient. Comparison of the structures and the mechanical responses of the two polymorphs revealed that the thermosalient effect of form I was due to reversible closing and opening of the arms of the diester molecules in a tweezer-like action.